The implementation of gender equality policies: Lithuanian and Swedish cases analysis - Ulickaitė, Viktorija (Information & Media, 2017)
Gender equality is related to equal opportunities for both women and men, who equally participate in public and private spheres of life. Stereotypical thinking and patriarchal attitudes are a result of discrimination against gender, regarding the equal pay disproportion of male and female workers, unequal employment opportunities and a lack of women in decisive positions within workplaces. Problems of gender equality do not only focus on national state agendas, but are also strongly supported on levels both international and the EU (gender mainstreaming is one of the most important goals included in the “Europe 2020” strategy). In order to achieve gender equality in various spheres of life, there is a need to ensure equal opportunities for both sexes not only de jure, but de facto as well. Gender equality policies in Lithuania are becoming more important; however, the results achieved are still scarce, whereas the implementation of gender equality policies in the Scandinavian countries are consistent and these practices should serve as guidelines. This paper examines the implementation of Lithuanian and Swedish gender equality policies. Sweden has been chosen as a good practice example in a comparative context with Lithuania, because its achievements in the field of gender equality are recognized as the best among the EU member states in 2015. The comparison of Sweden’s, as of a country’s that has achieved the most in implementing gender equality policies, and Lithuania’s practices helped to discover the similarities and differences that could lead to an achievement of better results in the field of gender equality. In addition, Lithuania’s reglaments of gender equality policies are similar to those of Sweden; however, there is still a lack of policy consistency. Therefore, a gap between formal and real gender equality appears. Both Lithuania and Sweden have highly institutionalized gender equality policies with increasing attention given to gender problems, but a lack of political will is the result of ineffective policy implementation, resulting in the questions regarding gender equality being pushed down on the list of priorities in Lithuania’s political agenda. The subject of this paper is the implementation of gender equality policy. Consequently, the goal of the paper is to compare how gender equality policies are implemented in Lithuania and Sweden. To reach this goal, such objectives are set: to present gender equality policy, analyze gender equality implementation in Lithuania, analyze gender equality implementation in Sweden and to compare the gender equality policies in both countries. A comparison of Sweden’s, as of a country’s that has achieved the most in implementing gender equality policy, and Lithuania’s practices helped to discover the similarities and differences that could lead to an achievement of better results in the field of gender equality. In addition, Lithuania’s reglaments of gender equality policy are similar to those of Sweden; however, there is still a lack of policy consistency. Therefore, a gap between formal and real gender equality appears. Both Lithuania and Sweden have highly institutionalized gender equality policies with increasing attention being given to gender problems.
Keywords: ...